CONSUMPTION OF RURAL HOUSEHOLDS IN FOOD AND NOURISHMENT IN MAHARASHTRA STATE, INDIA (International Journal of Food and Nutritional Sciences, 2022)
Among the Indian states, Maharashtra has the highest rate of malnutrition. According to information provided by the state to the Bombay High Court, 6,582 kids perished from starvation between April of 2019 and April of 2022. In an affidavit submitted in April 2022, the state administration acknowledged that during these 39 months, the number of children with severe acute malnutrition increased by over 26,000 while the number of children with intermediate acute malnutrition increased by over one lakh. Almost 33 lakh youngsters in India are malnourished as of November 2021, which creates a somber and depressing backdrop to the country's 75th independences and discussions of a rapidly growing economy. According to data given by the Women's Health Initiative, more than half are extremely malnourished.